Advances in management accounting. Vol. 31 - Burney, Laurie L.; Malina, Mary A. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Advances in Management Accounting (AIMA) is a publication of quality applied research in management accounting. The journal's purpose is to publish thought-provoking articles that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners. As one of the premier management accounting research journals, AIMA is well-poised to meet the needs of management accounting scholars.Featured in Volume 31 are articles on:Competitor monitor and revenue management in hotels; The tie between CEO compensation and the 2008 financial crisis; The inclusion of qualitative measures in CEO incentive compensation; The association between performance-based pay and employee honesty; Managerial ability's linkage to earnings management within discontinued operations; Cash-to-cash and its association with long-term profitability in the manufacturing industry.
Prelims -- Competitor monitoring and revenue performance: evidence from the hospitality industry -- An empirical examination of economic determinants of financial CEO compensation: a comparative study on pre- and post-financial crisis periods -- Firm performance implications of using qualitative criteria in CEO bonus contracts -- Performance-based pay, performance monitoring, and dishonest behavior: the plot thickens -- The role of managerial ability in classification shifting using discontinued operations -- Cash-to-cash (C2C) length: insights on present and future profitability and liquidity.
Print version record
Keywords: Managerial accounting; Business & Economics -- Accounting -- Managerial; Management accounting & bookkeeping